Hydrothermal synthesis of hydroxyapatite nanorods using a fruit extract template (2018)
ABSTRACT: Biocompatible materials development for the replacement of human body parts has been one of the needs of science. Hydroxyapatite is a bioceramic similar to the mineral component present in the human hard tissues and animal body. In this work, hydroxyapatite nanorods were synthesized and characterized using a hydrothermal reaction with templates of fruit extracts in order to control the particles size and morphology. The powders obtained were characterized by scanning electron microscopy, X-ray diffraction, and infrared spectroscopy. Hydroxyapatite nanorods were obtained with diameters between 43.47 and 48.56 nm and lengths between 148.47 and 265.96 nm. For all assays, an adequate HA synthesis was confirmed because the XRD showed the main and secondary peaks. The crystallite size was calculated with the Scherrer equation, obtaining values between 5.99 and 6.96 nm and percentages crystallinity between 55.61 and 65.9%. The synthesized material can be a suitable biomaterial for the manufacture of bone substitutes.